2006
DOI: 10.1111/j.1464-410x.2005.05988.x
|View full text |Cite
|
Sign up to set email alerts
|

The functional effects of a c‐kit tyrosine inhibitor on guinea‐pig and human detrusor

Abstract: OBJECTIVE To describe the effect of a specific c‐kit receptor inhibitor (imatinib mesylate) on human detrusor strips in vitro and guinea‐pig cystometry in vivo, and to show histological data suggesting differences in the distribution of interstitial cells of Cajal (ICC)‐like cells in ‘normal’ and overactive human detrusor, as these cells have been identified as possible mediators of spontaneous activity and excitability in bladder smooth muscle. MATERIALS AND METHODS Specimens of human detrusor were stained im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
4
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 24 publications
6
111
4
3
Order By: Relevance
“…In patients with diabetes, decreased BICCs were observed and this was suggested to contribute to incontinence (74). Alterations to BICC function have also been reported in OAB and obstructed bladder in both humans and animal models (79,92,(94)(95)(96)(97). Increased expression of connexin 43 has been reported in patients with OAB, suggesting increased signal transduction between BICCs and BSM cells, potentially leading to motility problems (98,99).…”
Section: Bladder Icc: An Old Cell Newly Implicated In Lower Urinary Tmentioning
confidence: 99%
“…In patients with diabetes, decreased BICCs were observed and this was suggested to contribute to incontinence (74). Alterations to BICC function have also been reported in OAB and obstructed bladder in both humans and animal models (79,92,(94)(95)(96)(97). Increased expression of connexin 43 has been reported in patients with OAB, suggesting increased signal transduction between BICCs and BSM cells, potentially leading to motility problems (98,99).…”
Section: Bladder Icc: An Old Cell Newly Implicated In Lower Urinary Tmentioning
confidence: 99%
“…Therefore, although the location of boundary interstitial cells seems to be ideal to drive the bulk of smooth muscles, they clearly are not electrical pacemaker cells. However, experiments in which Glivec, a kit receptor antagonist, has been applied, show reduction in the activity of both isolated whole bladders [34][35][36] and the contractile and electrical activity of strips of detrusor, suggesting that interstitial cells may be in some way involved in the integration of activity. Interstitial cells are also found in the submucosa, close to the urothelium and the suburothelial sensory nerves, [37][38][39] where they may play a similar role in integrating activity.…”
Section: Sexual and Lut Function Af Brading Et Almentioning
confidence: 99%
“…Moreover, imatinib mesylate (Glivec), an inhibitor of Kit receptor tyrosine kinase, was more potent in inhibiting evoked and spontaneous contractions in overactive bladder than in normal bladder, and also improved parameters of cystometry. [34][35][36] ICC are thought to be involved in neuromuscular transmission, including inhibitory transmission mediated by NO; 45,46 therefore, they may also play an important role in the nerve-mediated modulation of detrusor smooth muscle excitability. Following stimulation with sodium nitroprusside, interstitial Sexual and LUT function AF Brading et al cells throughout the bladder demonstrated an intense induction of cGMP immunoreactivity, but detrusor muscle cells remained uniformly negative.…”
Section: Possible Role Of Interstitial Cells In Lutsmentioning
confidence: 99%
“…Because it has been reported that the number of interstitial cells is increased in a guinea-pig model of BOO (15) and that c-kit tyrosine kinase inhibitors, which inhibit interstitial cell activity, decreased the amplitude of spontaneous contractions in the guinea-pig and human bladder (16,17), interstitial cells may also be involved in the emergence of detrusor overactivity because of enhanced autonomous detrusor muscle activity.…”
Section: Increased Myogenic Activity Of Detrusor Smooth Musclesmentioning
confidence: 99%